Communication—Design, Development, and Evaluation of a High Resolution, Customizable 3D-Printed Flow-Type Electrochemical Microcell. Issue 12 (10th August 2020) - Summers, Kodi; Chidambaram, Dev
Abstract : Advances in 3D-printing technology was used to design and develop a customizable flow-type electrochemical microcell with analytical resolution similar to conventional glass capillary-based microcells. The advantages of this design are better and easier reproducibility, increased durability, and better control over design parameters. 3D printing was combined with conventional machining to enable rapid prototyping and testing of various flow designs and apertures sizes. Results from potentiodynamic polarization of copper demonstrated repeatability and accuracy in spatial resolution. Reproducibility of experimental area had 1.9% variation between different spots. The ease of use and endurance of the design was demonstrated through repeated use.